Hierarchy in international law the place of human rights - De Wet, Erika; Vidmar, Jure. (Oxford : Oxford University Press, 2012)
The existence of a hierarchy between the different international legal rules is increasingly being debated. This volume will identify the extent to which judicial bodies and domestic courts contribute to an emerging normative hierarchy within international law, based on the primacy of human rights.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Human rights; Hierarchies; Law